Electroanalysis of Fentanyl and Its New Analogs: A Review - Choińska, Marta Katarzyna; Šestáková, Ivana; Hrdlička, Vojtěch; Skopalová, Jana; Langmaier, Jan; Maier, Vítězslav; Navrátil, Tomáš (Biosensors, 2022)
The review describes fentanyl and its analogs as new synthetic opioids and the possibilities of their identification and determination using electrochemical methods (e.g., voltammetry, potentiometry, electrochemiluminescence) and electrochemical methods combined with various separation methods. The review also covers the analysis of new synthetic opioids, their parent compounds, and corresponding metabolites in body fluids, such as urine, blood, serum, and plasma, necessary for a fast and accurate diagnosis of intoxication. Identifying and quantifying these addictive and illicit substances and their metabolites is necessary for clinical, toxicological, and forensic purposes. As a reaction to the growing number of new synthetic opioid intoxications and increasing fatalities observed over the past ten years, we provide thorough background for developing new biosensors, screen-printed electrodes, or other point-of-care devices.
Keywords: Analgesics, Opioid; fentanyl; opioidní analgetika; Fentanyl